Kesantunan Berbahasa Pramuniaga dalam Melayani Konsumen di Toko Buku Sari Anggrek Padang - Sulastutik, Sulastutik; Amir, Amril; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This study aims to (1) describe the types of speech acts courtesy clerk in serving consumers when buying and selling bertansaksi Bookstore Sari Orchids in Padang. (2) identify the principles of politeness used salesclerk in serving consumers based on linguistic politeness. This research is a qualitative study using descriptive because this study aimed to describe the data obtained from the field or informants. The data captured on the "linguistic politeness in Serving Buyers Clerk Bookstore Padang Sari Orchid". The research data is linguistic politeness in Serving Buyers Clerk Bookstore Sari Orchid Padang. Data were analyzed with data analysis techniques as follows: (1) identifying and classifying the speech acts used clerk ilokusi in serving consumers. (2) analyze the types of speech acts and politeness in speech acts saleswoman consumers. (3) menabulisasikan speech acts and politeness in.